Perusahaan Tambang Batubara Tbk (IDX-Listed) Indonesia: Gaya Kepemimpinan Breakthrough Siknifikan Menaikkan Kinerja Organisasi melalui Kepuasan Karyawan - Joko Triraharjo; Havidz Aima; Achmad Hidayat Sutawidjaya; Ahmad Badawi Saluyv (Universitas Islam Bandung, 2021)
Indonesia is the largest coal exporter in the world. Indonesia's total coal production in 2018 was 528 million tons. Of this amount, 320 million tons were produced by coal mining companies listed on the Indonesia Stock Exchange. The phenomenon of the performance of coal mining companies in Indonesia which has been established in the period 2014 to 2018 there is a very high difference, both in terms of financial performance and the resulting production. The difference in the performance gap is thought to be influenced by the leadership style in the company. The purpose of this study is to analyze the effect of transformational leadership style, servant and breakthrough leadership on organizational performance with employee satisfaction as an intervening variable in coal mining companies listed on the Indonesia Stock Exchange and suggest implications for improving company performance. The respondents of this study were 15 coal mining companies listed on the Indonesian stock exchange. The type of research used is a quantitative method with 201 respondents, in supervisory to director positions. Data were analyzed using Structural Equation Model (SEM – AMOS). The results of the study indicate that the current speed of change in organizational behavior, technology and the business environment in the coal mining sector in Indonesia requires a change in the existing leadership style towards breakthrough leadership with 5 (five) dimensions, so that in its implication in the coal industry sector the existing leaders Currently, more emphasis is placed on changing leadership styles to become “multi power leaders” and “visionary leaders” and this will significantly increase organizational performance through employee satisfaction.